A Comparative Analysis of the Legal System on the Performance of Islamic Banks: A Study in the United Kingdom, Malaysia and Indonesia - Roqiyul Ma’arif Syam; Mabruri Andatu; Abdul Muiz Abdul Wadud (UIN Siber Syekh Nurjati Cirebon, 2025)
This research is motivated by the issue of the influence of the legal system on the performance of Islamic banks in three countries with different legal and social backgrounds, namely the United Kingdom (UK), Malaysia and Indonesia. A qualitative-comparative approach is used by focusing on the substantive and procedural legal system aspects that affect the operation of Islamic banks, as well as on performance indicators such as financial stability, operational efficiency, and the level of public trust. The results show that Malaysia has the most supportive legal system for the development of Islamic banks through its dual banking system framework, formal recognition of sharia principles, and integrated regulatory and supervisory institutions. While Indonesia has made progress in the regulatory aspect, it still faces challenges in harmonization between national law and sharia principles, as well as supervisory effectiveness. On the other hand, the UK, despite having a stable legal system, has not provided a sufficient legal basis to support the full operation of Islamic banks, as its regulatory approach is religion-neutral. This research also emphasizes the importance of legal culture and socio-religious context in supporting the performance of the Islamic finance industry. The practical implications of this research include the need for regulatory harmonization, institutional capacity building, and the establishment of international sharia law standards. Thus, strengthening the legal system that is responsive to sharia principles is a strategic key in strengthening the competitiveness of Islamic banks globally.Keywords: Legal system; United Kingdom; Indonesia; Malaysia; Islamic Bank.